Towards the introduction of QoS information in a component model - Sun, Meng (2010)
Assuring Quality of Service (QoS) properties is critical in the development of component-based distributed systems. This paper presents an approach to introduce QoS constraints into a coalgebraic model of software components. Such constraints are formally captured through the concept of a Q-algebra which, in its turn, can be smoothly integrated in the definition of component combinators.